A Study to Examine the Factors Contributing Towards Financial Management Behavior Among Non-Finance Students in AIMST University, Kedah (Journal of Entrepreneurship and Business, 2024)
This paper aims to examine the factors contributing to financial management behavior among non-finance students at AIMST University, Kedah. The dependent variable is financial management behavior while the independent variables are financial literacy, family’s social status, and financial self-efficacy. The data for this study was collected through the distribution of self-administered questionnaires. The population for this research is undergraduate non-finance students at AIMST University. The data collected were analysed using descriptive analysis, reliability analysis, Multiple Linear Regression Analysis, and Pearson Correlation Coefficient Analysis. The findings of this research revealed that financial literacy, family social status, and financial self-efficacy have significant relationships with financial management behaviour.
Keywords: Array; Array; Array; Array